Interactions between irradiation defects and nitrogen in α‐Fe: an integrated experimental and theoretical study. (15th October 2022) - Theodorou, Andreas; Syskaki, Maria-Andromachi; Kotsina, Zoi; Axiotis, Michail; Apostolopoulos, George; Fu, Chu-Chun
Graphical abstract: Abstract: This paper aims at clarifying, by means of an integrated experimental and theoretical approach, the properties of the interaction between interstitial nitrogen (N) and irradiation generated lattice defects in α -Fe. For this purpose, N-doped and pure Fe specimens were irradiated at low temperature by high energy protons. The evolution of radiation defects and their interaction with N was monitored by electrical resistivity measurements during post-irradiation annealing. In parallel, density functional theory (DFT) was employed to study the properties of N solutes, vacancies and their mutual interaction in the Fe matrix. The DFT results were confronted to the experiment via kinetic rate theory modelling, employed to quantitatively simulate the measured resistivity evolution. One of the most important results is the experimental validation of the theoretically predicted strong binding energy of vacancy-N complexes, which reconciles previous discrepancies. Furthermore, a quantitative interpretation is provided of how irradiation competes with nitride precipitation.